Pazopanib plus cetuximab in recurrent or metastatic head and neck squamous cell carcinoma: an open-label, phase 1b and expansion study - Adkins, Douglas (Lancet Oncol, 2018)
BACKGROUND: Angiogenesis is a hallmark of head and neck squamous cell carcinoma (HNSCC), and a mechanism of resistance to EGFR inhibition. We investigated the safety and potential activity of pazopanib, an angiogenesis inhibitor, plus cetuximab, an EGFR inhibitor, in patients with recurrent or metastatic HNSCC. METHODS: We did an open-label, single-centre, dose-escalation phase 1b trial using a standard 3 + 3 design, followed by an expansion cohort phase. Eligible participants were patients with histologically or cytologically confirmed recurrent or metastatic HNSCC, aged at least 18 years, had measurable disease as per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, and an Eastern Cooperative Oncology Group performance status of 0–1. During dose escalation, pazopanib oral suspension was administered daily in 8-week cycles at doses of 200 mg/day, 400 mg/day, 600 mg/day, or 800 mg/day, with cetuximab given intravenously once per week (400 mg/m(2) first dose and 250 mg/m(2) in consecutive cycles). The primary endpoint was to determine the maximum tolerated dose or recommended phase 2 dose of pazopanib in combination with cetuximab. Analyses were done per protocol. This trial is registered with ClinicalTrials.gov, number NCT01716416, and it is ongoing but closed to accrual. FINDINGS: Between June 5, 2013, and April 4, 2017, we enrolled 22 patients into the phase 1b, dose-escalation phase of the trial. A maximum tolerated dose of pazopanib in combination with cetuximab was not reached. Single dose-limiting toxic events (all grade 3) during dose escalation occurred with pazopanib 400 mg/day (neutropenia with infection), 600 mg/day (proteinuria), and 800 mg/day (fatigue). The established recommended phase 2 dose for the combination was 800 mg/day of pazopanib during cycles of 8 weeks each, plus cetuximab 400 mg/m(2) on day 1 of cycle 1, then cetuximab 250 mg/m(2) weekly. A further nine patients were enrolled into the expansion cohort and treated with the established recommended phase 2 dose. The most common (grade 3–4) adverse events for all patients were hypertension (ten [32%] of 31), lymphocyte count decrease (seven [23%]), and dysphagia (seven [23%]). There were no treatment-related deaths. 11 (35%; 95% CI 19·2–54·6) of 31 patients achieved an overall response, as assessed by the investigator; two (6%) had a complete response and nine (29%) a partial response. Tumour responses were also observed in six (55%) of 11 patients with platinum-naive and cetuximab-naive disease, three (25%) of 12 patients with cetuximab-resistant disease, and five (28%) of 18 patients with platinum-resistant disease. INTERPRETATION: Pazopanib oral suspension at a dose of 800 mg/day was feasible to administer in combination with standard weekly cetuximab for patients with recurrent or metastatic HNSCC. Encouraging preliminary antitumour activity was observed with this combination therapy and warrants further validation in randomised trials. FUNDING: GlaxoSmithKline and Novartis.